Pengaruh Torefaksi terhadap Sifat Kimia Pelet Tandan Kosong Kelapa Sawit - Irma Thya Rani; Wahyu Hidayat; Indra Gumay Febryano; Dewi Agustina Iryani; Agus Haryanto; Udin Hasanudin (The University of Lampung, 2020)
ABSTRACT Palm oil (Elaeis guineensis) is one of the agricultural biomass. Palm oil solid waste that is relatively easy to find is empty fruit bunches (EFB). EFB biomass is converted into pellets to get a uniform size, then heated through torrefaction into bioenergy so that its utilization is more optimal and can increase economic value. Torrefaction is slow heating of biomass with a temperature range of 200oC-300oC with a state of little oxygen or without oxygen. Torrefaction was carried out using an electric furnace with a target temperature of 280oC and a duration of 20 minutes. The purpose of this paper is to determine the effect of torrefaction on the chemical properties of EFB pellets. The results of this study are hemicellulose and cellulose decreased by 0,58% - 0,77%, this happens because hemicellulose and cellulose are degraded with increasing temperature and time of torrefaction. This is confirmed by changes in the line spectrum for FT-IR analysis where C-O, C=C, C-H, and O-H experience changes in the line spectrum that indicate changes in chemical composition. while lignin increased after torrefaction by 2,71%. Water content in EFB pellets decreased by 0,65%, while EFB pellets without treatment (control) by 14,95% after torrefaction became 22,70%. The volatile content of EFB control pellets was 69,55% after torrefaction to 61,21% so that the fixed carbon content of EFB control pellets was 10,03% and EFB pellets after torrefaction became 14,23%. The heat value of EFB pellets before torrefaction is 15,82 MJ/kg, and after torrefaction, the heating value increases to 18,28 MJ/kg so that it reaches the standard requirements of SNI 8675: 2018 as biomass pellets. Torrefaction pellets from EFB can provide a large increase in the quality of the bioenergy chemical properties. Biomass torrefaction is very suitable for combustion in power plants and home industries. Keywords:Chemical composition, FTIR,oil palm empty fruit bunches, torrefaction ABSTRAK Kelapa sawit (Elaeis guineensis) merupakan salah satu biomassa hasil pertanian. Limbah padat perkebunan sawit yang relatif mudah dijumpai ialah tandan kosong kelapa sawit (TKKS). Biomassa TKKS dikonversikan menjadi pelet untuk mendapatkan ukuran yang seragam, kemudian ditorefaksi untuk digunakan sebagai bioenergi sehingga pemanfaatannya lebih optimal dan dapat meningkatkan nilai ekonomi. Torefaksi merupakan pemanasan biomassa secara perlahan dengan kisaran suhu 200oC – 300oC dengan keadaan sedikit oksigen bahkan tanpa oksigen. Torefaksi dilakukan menggunakan electric furnace dengan target suhu 280oC dan durasi selama 20 menit. Tujuan dari penelitian ini ialah untuk mengetahui pengaruh torefaksi terhadap sifat kimia pelet TKKS. Hasil dari penelitian ini ialah kadar hemiselulosa dan selulosa menurun sebesar 0,58% - 0,77% hal tersebut terjadi karena hemiselulosa dan selulosa terdegradasi seiring dengan peningkatan suhu dan waktu torefaksi. Hal tersebut diperkuat dengan perubahan gugus fungsi terhadap analisis FT-IR dimana gugus C-O, C=C, C-H, dan O-H mengalami perubahan spektrum garis pita yang menandakan adanya perubahan komposisi kimia. Sedangkan kadar lignin meningkat setelah torefaksi sebesar 2,71%. Kadar air pada pelet TKKS menurun sebesar 0,65 %, sedangkan abu pelet TKKS tanpa perlakuan (kontrol) sebesar 14,95% setelah tertorefaksi menjadi 22,70. Zat terbang pelet TKKS kontrol sebesar 69,55% setelah tertorefaksi menjadi 61,21% sehingga diperoleh nilai karbon terikat pelet TKKS kontrol sebesar 10,03% dan pelet TKKS yang tertorefaksi sebesar 14,23%. Nilai kalor pelet TKKS sebelum torefaksi sebesar 15,82 MJ/kg, dan setelah torefaksi nilai kalor meningkat menjadi 18,28 MJ/kg sehingga memenuhi SNI 8675:2018 pelet biomassa. Pelet TKKS yang tertorefaksi dapat memberikan peningkatan besar dalam kualitas sifat kimia bioenergi. Biomassa yang tortorefaksi sangat cocok untuk pembakaran di pembangkit listrik dan industri. Kata Kunci: FTIR,komposisi kimia,tandan kosong kelapa sawit, torefaksi